MAKNA SIMBOLIS GERAK TORTOR DALAHI DAN DABORU DALAM KONTEKS UPACARA PERNIKAHAN PADA MASYARAKAT SIMALUNGUN DI DESA SIPISPIS - Dian Lestari Saragih Lestari Saragih (Gesture: Jurnal Seni Tari, 2013)
The research was filmed in the village of Sipispis sub-district of Serdang Bedagai Regency Sipispis. While the research was carried out in June 2013 to August 2013. The methods used in this study is the method deskriftif with qualitative data, collected through observation, interviews, literature studies and documentation. Based on the results of the study, found the results that a tortor in Simalungun wedding ceremony can be identified based on the movements of dance, the male and female dance called dalahi and daboru tortor. The community was very prominent tortor Simalungun, because tortor serves as a communication medium through movement. Dalahi and daboru in Tortor wedding ceremony Simalungun society has a symbolic meaning so profound, because dalahi and daboru tortor is derived from the results of the thinking of society, based on the Community Customs Simalungun Simalungun.